Antimicrobial effect of calcium hydroxide as endo intracanal dressing on Streptococcus viridans - Nanik Zubaidah (Dental Journal (Majalah Kedokteran Gigi), 2008)
Calcium hydroxide had been used as the intra-canal dressing in endodontic treatment due to its high alkaline and antimicrobial capacity. It can also dissolve the necrotic tissue, prevent dental root resorbtion and regenerate a new hard tissue. The aim of this study was to determine the concentration of calcium hydroxide which had the highest antimicrobial effect on Streptococcus viridans. Samples were divided into 5 groups; each group consisted of 8 samples with different concentration of calcium hydroxide. Group I: 50%, group II: 55, Group III: 60%, Group IV: 65%, Group V: 70%. The antimicrobial testing was performed using diffusion method against Streptococcus viridans. The result of susceptibility test was showed by the inhibition zone diameter which measured with caliper (in millimeter). We analyzed the data using One-Way ANOVA test with significant difference 0.05 and subsequently LSD test. The study showed that calcium hydroxide with concentration 60% has the highest antimicrobial effect.